Comparison of astaxanthin and oxidized  - carotene in red tilapia diets: Effects on growth, pigmentation, immunity, and antioxidative functions - Duangjai, Shakriya; Jintasataporn, Orapint; Kokau, Sarinpan; Saetang, Tachin; Therdthai, Nantawan (Edelweiss Applied Science and Technology, 2024)
The study explored the effect of astaxanthin (AX) and oxidized b-carotene (OX) on the growth performance, skin coloration, and hematological parameters of red tilapia (Oreochromis spp.). The tilapia were fed one of three treatments: (a) commercial control diet, (b) commerical control diet supplemented with astaxanthin, and (c) commercial control diet supplemented with oxidized b-carotene. The experminet was based on a completely randomized design (CRD). Each treatments had three replicates. Red tilapia with an initial mean weight at 42.34 ± 1.326 grams per individual were distributed 8 fish per replicate: in total 72 fish. The feed was fed at a rate of 1.5% of body weight three times a day. Results indicated that fish fed the OX diet exhibited numerically superior growth performance compared to those fed the AX diet and control diets. Furthermore, fish fed the OX diet had significantly enhanced skin carotenoid pigmentation (p<0.05). Hematological analysis revealed significantly higher levels of superoxide dismutase (SOD) and lysozyme activity in fish fed the OX diet compared to the other diet groups (p<0.05). Therefore, it can be concluded that the fish fed the OX diet tended to outperform the fish fed AX diet and control diet and exhibited significantly better coloration and antioxidant status in this study.